2020
DOI: 10.3171/2019.5.jns19313
|View full text |Cite
|
Sign up to set email alerts
|

Early postmarket results with PulseRider for treatment of wide-necked intracranial aneurysms: a multicenter experience

Abstract: OBJECTIVETraditionally, stent-assisted coiling and balloon remodeling have been the primary endovascular treatments for wide-necked intracranial aneurysms with complex morphologies. PulseRider is an aneurysm neck reconstruction device that provides parent vessel protection for aneurysm coiling. The objective of this study was to report early postmarket results with the PulseRider device.METHODSThis study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…A total of 63 aneurysms were treated and although it seems ‘safe and probably effective’ for treating intracranial bifurcation aneurysms, a bigger sample size is needed to support this statement 23. More recently, Srinivasan et al 24 reported early postmarket results across 13 centres in the USA for the treatment of 54 aneurysms. Both clinical and radiographic outcomes were comparable with early studies with technical success in 52 cases (96.2%), major complications in three cases and immediate Raymond I or II occlusion in 69.1%.…”
Section: Advances In Stent-assisted Coilingmentioning
confidence: 99%
“…A total of 63 aneurysms were treated and although it seems ‘safe and probably effective’ for treating intracranial bifurcation aneurysms, a bigger sample size is needed to support this statement 23. More recently, Srinivasan et al 24 reported early postmarket results across 13 centres in the USA for the treatment of 54 aneurysms. Both clinical and radiographic outcomes were comparable with early studies with technical success in 52 cases (96.2%), major complications in three cases and immediate Raymond I or II occlusion in 69.1%.…”
Section: Advances In Stent-assisted Coilingmentioning
confidence: 99%
“…Large multicenter studies have allowed for the treating surgeon to follow with their imaging modality of choice. 2,3 This case report implies that MRA is appropriate for follow-up aneurysms but not necessarily the parent vessel.…”
Section: Discussionmentioning
confidence: 86%
“…Endovascular treatment of widenecked cerebral aneurysms with the PulseRider has a high technical success rate, and there is complete occlusion of approximately two-thirds of aneurysms at one-year after treatment and adequate occlusion of 90% at one-year. 2,3 Additionally, the PulseRider is composed of less metal than a traditional stent with larger fenestrations, which may allow for easier coiling.…”
Section: Introductionmentioning
confidence: 99%
“…We included six studies in the qualitative and quantitative syntheses (Figure 1). There were a total of 157 subjects from six studies 4,5,710 (Table 1). Out of these studies, one was a retrospective cohort study, two were single-arm registries, one was a single-arm clinical trial, and two were case series.…”
Section: Resultsmentioning
confidence: 99%
“…The scaffolding like-function of this device prevents the protrusion of endovascular coils even in the wide-necked anatomy and thus facilitating thrombus formation. 4 This device is also easier to deploy and requires fewer steps compared to Y-stent. Pulserider is a versatile device and can be positioned within the wings of daughter branches, this device also has a lower metal-to-artery ratio, which prevents jailing of daughter branches.…”
Section: Introductionmentioning
confidence: 99%